EFEKTIVITAS JAMINAN PENDIDIKAN DAERAH (JPD) DALAM MENURUNKAN ANGKA PUTUS SEKOLAH DI KOTA YOGYAKARTA - Kusuma, Dwi Widiawati Wijaya (Spektrum Analisis Kebijakan Pendidikan, 2021)
This research aims to determine the effectiveness of the Regional Education Grant in reducing dropout rates in the City of Yogyakarta. The author explored the effectiveness of the Regional Education Grant on its role in reducing dropout rates, so the author explores Regional Education Grant rights in their role in reducing dropout rates for the last 5 years (2015-2019). This research adopted a descriptive quantitative research, this research described the situation that occurred, without testing the hypothesis with secondary data analysis methods which were complemented by the interview method. The population in this research were dropout rates in the city of Yogyakarta during the last 5 years. The data analyses used the regression coefficient analysis and the determination coefficient analysis. The result of this research is that the education security program can not be said to be effective, especially in reducing the dropout rates. The tendency causes were the problems of achievement program that were not maximized yet, especially due to the external factors such as the achievement of Regional Education Grant goals unsupport by public. For example, there was a missunderstanding information, which lead to the highest reason for dropping out rates in the City of Yogyakarta. It was actually triggered by a lack of motivation to learn so that the students were reluctant to go to school, with a percentage of 29.70%.